Mathematical calculations of iron complex stoichiometry by direct UV-Vis spectrophotometry - Filipský, Tomáš; Říha, Michal; Hrdina, Radomír; Vávrová, Kateřina; Mladěnka, Přemysl (Bioorganic chemistry, 2013)
The effects of iron-chelating agents on miscellaneous pathologies are currently largely tested. Due to various indications, different properties for chelators are required. A stoichiometry of the complex in relation to pH is one of the crucial factors. Moreover, the published data on the stoichiometry, especially concerning flavonoids, are equivocal. In this study, a new complementary approach was employed for the determination of stoichiometry in 10 iron-chelating agents, including clinically used drugs, by UV-Vis spectrophotometry at relevant pH conditions and compared with the standard Job's method. This study showed that the simple approach based on absorbance at the wavelength of complex absorption maximum was sufficient when the difference between absorption maximum of substance and complex was high. However, in majority of substances this difference was much lower (9-73 nm). The novel complementary approach was able to determine the stoichiometry in all tested cases. The major benefit of this method compared to the standard Job's approach seems to be its capability to reveal a reaction stoichiometry in chelators with moderate affinity to iron. In conclusion, using this complementary method may explain several previous contradictory data and lead to a better understanding of the underlying mechanisms of chelator's action.
Keywords: Models, Chemical; chelátory; spektrofotometrie ultrafialová; železité sloučeniny; Ferrous Compounds; Spectrophotometry, Ultraviolet; koncentrace vodíkových iontů; Chelating Agents; Hydrogen-Ion Concentration; chemické modely; Ferric Compounds; železnaté sloučeniny